Salicylate elimination diets in children: is food restriction supported by the evidence?. Issue 11 (17th June 2013) - Gray, Paul E A; Mehr, Sam; Katelaris, Constance H; Wainstein, Brynn K; Star, Anita; Campbell, Dianne; Joshi, Preeti; Wong, Melanie; Frankum, Brad; Keat, Karuna; Dunne, Geraldine; Dennison, Barbara; et al.
Abstract: A review of case notes from our Sydney‐based paediatric allergy services, between 1 January 2003 and 31 December 2011, identified 74 children who had been prescribed diets that eliminated foods containing natural salicylates before attending our clinics. The most common indications for starting the diets were eczema (34/74) and behavioural disturbances (17/74) including attention deficit hyperactivity disorder (ADHD). We could find no peer‐reviewed evidence to support the efficacy of salicylate elimination diets in managing these diseases. We do not prescribe these diets, and in a survey of European and North American food allergy experts, only 1/23 respondents used a similar diet for eczema, with none of the respondents using salicylate elimination to treat ADHD. A high proportion (31/66) of children suffered adverse outcomes, including nutritional deficiencies and food aversion, with four children developing eating disorders. We could find no published evidence to support the safety of these diets in children. While this uncontrolled study does not prove a causal relationship between salicylate elimination diets and harm, the frequency of adverse events appears high, and in the absence of evidence of safety or efficacy, we cannot recommend the use of these diets in children.